Aspek Hukum Waralaba dan Permasalahannya di Indonesia - Arisandi, Moh Rivai Arisandi (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2025)
The main purpose of this study is to understand and examine how franchise business activities operate in Indonesia and to identify their legal issues from the perspective of positive law. The concept of franchising has become a significant trendsetter, bringing a distinct influence to the domestic economic landscape. In order for franchising to develop and serve as an embryo for national economic growth, it is essential to establish legal certainty that binds all business actors both franchisors and franchisees. Therefore, franchise cooperation between parties must be based on a written agreement governed by the applicable laws and regulations. This research employs a normative juridical approach (normative legal research), with data collected through literature study, namely by tracing, identifying, and analyzing legal sources and scholarly works relevant to the research topic. The findings indicate that the implementation of franchising in Indonesia already has a sufficiently strong legal foundation through Peraturan Pemerintah No. 35 Tahun 2024 and Peraturan Menteri Perdagangan No. 71 Tahun 2019. However, in practice, various legal problems still arise, particularly concerning the imbalance of bargaining positions between franchisors and franchisees, which often results in adhesion contracts and potential breaches of contract (default). This study concludes that the implementation of franchising in Indonesia has not yet fully complied with the existing legal provisions. Although the regulations are clearly stipulated under PP No. 35 tahun 2024 and Permendagri No. 71 Tahun 2019, many business actors remain insufficiently informed about the substance of these laws and are more profit-oriented. Consequently, this situation gives rise to improper practices, such as unilateral termination of franchise agreements without valid legal grounds. Therefore, there is an urgent need to enhance legal awareness and compliance with the principles of justice and legal certainty in every stage of franchise agreement implementation and termination.